Analysis of the agroindustrial process and energy valuation of the african palm (Elaeis Guineensis Jacq) in Honduras - Torres Mejía, Fredy; Torres Mejía, Juan Alexander; Cantarero Reyes, Laura Mariela (Nexo Revista Científica, 2023)
The analysis of the African Palm (Elaeis Guineensis) process in Honduras was developed, elaborating the description of the process, and construction of the balance of matter in each of its stages, in Honduras there are 190,000 Ha of palm planted, being the second main crop of the country after coffee. In the process the product is received, it goes to the stage of sterilization of bunches of fresh fruit, then the rachis is fruited, and the solids are separated from the liquids of the part of the bunch of the palm, then it goes to clarification where the immiscible liquids and the residues that remain in the oil are separated to this process enters only the liquid part of the previous process with a certain value, To obtain the oil ready for refining, then it is passed to the defibration, here the solid part of the extraction process is taken and a usable product comes out for the next process, where they obtain the by-products of fiber and almond, then it goes to the recovery process of the almond formed by by-products of evaporation and shell; In the refining process the oil changes to pale yellow to yellow, which is subsequently passed to the filtrate consists of the mechanical discharge of the earth used in bleaching and maximum recovery of the oil. In the deodorized fatty acids salts, which finally follows the fractionation phase where they are fed with antioxidant to obtain RBD oil. From this crop can be obtained as primary energy 83655.94 MJ / ha.year, of the four main by-products, energy equivalent annual to 4.41TEP, and 13.62 Ton CO2 eq, and 31.75 BEP; the process of obtaining African palm oil produces a large amount of biomass, which must be used biofuels, since they represent a good source of clean energy.